Extraction of Residue Oil from Palm Oil Mill Effluent (POME) Using Organic Solvent - A. L. Ahmad; K. Sithamparam; M. M. D. Zulkali; S. Ismail (Universitas Gadjah Mada, 2003)
Palm oil industry in Malaysia has grown to become an important agriculture based industry and it is accounted for about 52% of the world palm oil output, which generated RM 13 billions export earning for the country. With increased cultivation and production of palm oil in the region, the disposal of the processed waste will become a major problem if it is not being treated properly. Palm oil mill effluent (POME) is extremely polluting with its high organic content. Oil and grease content in POME is 4,000 mg/L which is relatively high compared to the allowable limit by the Malaysian Department of Environment of only 50 mg/L. This paper describes the research results in removing oil and grease content for the POME using solvent extraction method. Six different organic solvents; n-hexane, n-heptane, benzene, petroleum ether, pentane and petroleum benzene were used. For every solvent the effect of solvent ratio, mixing time, mixing speed and pH were analyzed to determine the optimum condition for maximum extraction of oil. Results showed that n-hexane give the best performance in extracting oil from POME with solvent to POME ratio of 6:10. It was estimated about 0.54 grams of oil and grease per liter of POME can be extracted at optimum conditions; mixing speed of 200 rpm, 20 minutes mixing time and at pH 9.